Serological and molecular detection of Strongyloides stercoralis infection among an Orang Asli community in Malaysia - Arine Fadzlun, Ahmad; Faizah, Hadip; Romano, Ngui; Yvonne Ai, Lian Lim; Rohela, Mahmud (Springer Nature, 2013)
Detection of Strongyloides stercoralisinfection particularly in asymptomatic individuals is often hampered due to the lack of standard diagnostic tools. In this study, the use of serological and molecular approaches were investigated for the detection of S. stercoralis infection among an Orang Asli (indigenous) community following a preliminary detection by microscopic examination of faecal samples. Out of 54 individuals studied, 17/54 (31.5 %) were detected to be positive for S. stercoralis infection by enzyme-linked immunosorbent assay (ELISA), compared to 0/54 (0 %) by faecal examination. Further confirmation performed by a nested polymerase chain reaction (PCR) using DNA extracted from faecal samples of these 17 individuals yielded 3/17 (17.6 %) positives for S. stercoralis DNA amplification. No amplification was seen with the other 37 faecal samples, which were negative by microscopy and ELISA. As the high ELISA positive results were suspected to be false-positives, ELISA is not recommended for use as a detection tool but may be beneficial for evaluating the effectiveness of anti-Strongyloides drugs. The present finding indicated that PCR should be considered as an alternative diagnostic tool for the detection of S. stercoralis infection.